2015
DOI: 10.1039/c4sm02712d
|View full text |Cite
|
Sign up to set email alerts
|

On the formation of dendrimer/nucleolipids surface films for directed self-assembly

Abstract: We describe the formation and structure of nucleolipid/dendrimer multilayer films controlled by non-covalent interactions to obtain biomaterials that exhibit molecular recognition of nucleic acids. Layers of cationic poly(amidoamine) (PAMAM) dendrimers of generation 4 and the anionic nucleolipids 1,2-dilauroyl-sn-glycero-3-phosphatidylnucleosides (DLPNs) based on uridine (DLPU) and adenosine (DLPA) were first formed at the silica-water interface. The PAMAM/DLPN layers were then exposed to short oligonucleotide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 69 publications
0
7
0
Order By: Relevance
“…The IR beam was reflected through a trapezoidal silicon crystal (Crystran) with four of its six faces (the beam either traverses across or reflects from) polished to ∼3 Å rms roughness. General information about the use of this setup in solid-liquid interfacial studies can be found in Arteta et al (59).…”
Section: Model Membrane Fabrication For Neutron Reflectometry and Infmentioning
confidence: 99%
“…The IR beam was reflected through a trapezoidal silicon crystal (Crystran) with four of its six faces (the beam either traverses across or reflects from) polished to ∼3 Å rms roughness. General information about the use of this setup in solid-liquid interfacial studies can be found in Arteta et al (59).…”
Section: Model Membrane Fabrication For Neutron Reflectometry and Infmentioning
confidence: 99%
“…We present here a study performed with QCM-D, 6,[34][35][36][37][38][39] combined with NR 37,[40][41][42][43] aimed at exploring the effect of soft and hard protein coronas on the interaction of polystyrene (PS) NPs with supported lipid bilayers.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Berti and co‐workers reported the ability of NL bilayers to selectively bind single‐stranded nucleic acids . In another study, the binding between nucleotide lipid/dendrimer surfaces and oligonucleotides was reported . This system featured cationic poly(amidoamine) or PAMAM dendrimers ( Figure A), which formed films with negatively charged nucleotide lipids.…”
Section: Nucleolipidsmentioning
confidence: 99%
“…C) Sequential addition of dendrimers, DLPN, and nucleic acids allowing selective binding between the functionalized surface and nucleic acids. Reproduced with permission . Copyright 2015, Royal Society of Chemistry.…”
Section: Nucleolipidsmentioning
confidence: 99%